Experiencing Embodied Creativity through a Tangible Storytelling Artifact - Carbajal, Marleny Luque; Baranauskas, M. Cecília C. (Anais do Workshop de Informática na Escola (WIE); 2025: Anais do XXXI Workshop de Informática na EscolaDO - 10.5753/wie.2025.13009, 2025)
Embodied creativity claims that cognitive mechanisms involved in creativity, such as idea generation, conceptual combination, and mental imagery, are facilitated by embodied interaction with the environment. Storytelling serves as a powerful tool to foster communication, collaboration, and creative thinking. By combining innovative forms of storytelling and contemporary technologies, it is possible to design immersive creative experiences. This work aims to explore and understand the role of embodied interaction in children’s creative processes as they interact with Livro Mágico, a storytelling artifact designed to support meaningful story creation. We conducted a Case Study involving preschool teachers and children aged 5-6 in an educational setting. Participants collaborated to create physical representations of stories using NFC technology. Analysis of data collected shows how children’s interaction with the storytelling artifact mediated embodied narrative experiences, and encouraged collaboration and imagination.